Kinerja Auditor Kantor Inspektorat Kabupaten Kampar: Pengaruh Independensi, Profesionalisme, Gaya Kepemimpinan, Komitmen Organisasi, dan Pemahaman Good Governance : Auditor performance in the Kampar District Inspectorate: Influence of Independence, Professionalism, Leadership Style, Organizational Commitment and Understanding of Good Governance - Elvira, Yulia; Djamil, Nasrullah (JAWI : Journal of Ahkam Wa Iqtishad, 2024)
A frequent problem in the era of globalization is the increase in corruption, nepotism, and collusion affecting the people of the world. This is shown by the many findings of BPK examinations of weaknesses in the government's internal control system. In this case, the role of the government's internal auditor is expected to create an effective and sustainable control system. This study aims to determine the partial and simultaneous influence between independence, professionalism, leadership style, organizational commitment, and understanding of good governance on auditor performance at the Kampar District Inspectorate Office. This research is a quantitative research. The population and sample in this study are all auditors and district inspectorate ppupd. Kampar as many as 44 people. The data collection technique used is through questionnaires. The analytical technique used in this study is descriptive statistical analysis. The instrument is tested using validity tests, reliability tests, and normality tests. The data analysis technique used is multiple linear regression analysis. The results showed that understanding good governance has a positive effect on auditor performance. While independence, professionalism, leadership style, and organizational commitment negatively affect auditor performance.